(untitled) (Research, Society and Development, 2020)
The objective was to know the difficulties and facilities of nurses in adhering to self-care in relation to the risks of accidents at work. Qualitative, exploratory and descriptive research, conducted at a University Hospital in southern Brazil. Method: Data collection was performed in July 2018, through semi-structured interview. Data analysis took place through thematic analysis. Results: Regarding the difficulties, the participants highlighted the lack of time during the assistance, high demand from users, procedures, lack of awareness among professionals, the inappropriate use of Personal Protective Equipment, among others. Regarding facilities, they reported the availability of Personal Protective Equipment. Conclusion: it is highlighted that it is necessary to reflect on the subject, on the part of all involved in the assistance, because it is understood that the risks exist and their prevention needs to be encouraged through continuous education.